2013
DOI: 10.1073/pnas.1216436110
|View full text |Cite|
|
Sign up to set email alerts
|

Majority of differentially expressed genes are down-regulated during malignant transformation in a four-stage model

Abstract: The transformation of normal cells to malignant, metastatic tumor cells is a multistep process caused by the sequential acquirement of genetic changes. To identify these changes, we compared the transcriptomes and levels and distribution of proteins in a fourstage cell model of isogenically matched normal, immortalized, transformed, and metastatic human cells, using deep transcriptome sequencing and immunofluorescence microscopy. The data show that ∼6% (n = 1,357) of the human protein-coding genes are differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 37 publications
(36 reference statements)
12
54
0
Order By: Relevance
“…However, this should have diluted their overrepresentation in known cancer gene sets. In addition, using an isogenically matched cell model with three oncogenes added sequentially so as to mimic the expression divergences during cancer, a previous study found that B80% of the differentially expressed genes are downregulated 25 . We analysed these genes and found that they are highly enriched in multicellularity-related GO terms ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this should have diluted their overrepresentation in known cancer gene sets. In addition, using an isogenically matched cell model with three oncogenes added sequentially so as to mimic the expression divergences during cancer, a previous study found that B80% of the differentially expressed genes are downregulated 25 . We analysed these genes and found that they are highly enriched in multicellularity-related GO terms ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with an RNA integrity number (RIN) 49.5 (Agilent 2100 Bioanalyzer) were used. Poly(A) þ mRNA was isolated with Dynabeads Oligo(dT) 25 (Life Technology 61005). Libraries were constructed following the TruSeq RNA Guide (Illumina) and subject to Illumina GAII or HiSseq sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured as described previously [36]. These cells have been characterized previously with regard to their total gene transcription and protein expression, as well as the cytoskeletal organization and behavior of the cells [21,22,23]. For confocal and single-color STED experiments, the cells were transiently transfected with a plasmid coding for mCherry fused to the protein of interest, 24 h prior to analysis, as described previously [2].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in our study, we have used transformed, highly migratory, metastasizing human fibroblasts, which have a high endogenous level of vimentin. These cells have been well characterized, both due to quantitative analysis of the global transcriptome within these cells, and because the levels and localization of many proteins, as well as the cytoskeletal organization and behavior of the cells, have been described previously [21,22,23]. We also previously showed that these cells have reduced FA size, altered spatial distribution of cell-matrix adhesions, and a more entangled vimentin network compared to normal, primary fibroblast [23].…”
Section: Introductionmentioning
confidence: 99%
“…The transformation process of normal cells into malignant tumor cells is caused by sequence genetic mutations and consists of sequential stages in cascade [1]. The genome sequencing efforts have identified a large number of somatic genomic alterations and numerous germinal mutations associated with cancer predisposition.…”
Section: Introductionmentioning
confidence: 99%